Quality seed production of onion - Mahajan, Vijay; Gupta, A J; Thangasamy, A.; Gupta, A J; Gawande, S. J.; Singh, Major (Indian Horticulture, 2019)
Annually about 10,000 tonnes of onion seed is required. The organized sector including public and private produces only 30-40% of the total onion seed of improved varieties. The remaining seed is produced by farmers without observing any seed standards for isolation or varietal purity. Availability of quality seed material plays major role in increasing onion productivity. Hence, proper care should be taken from seed sowing to seed production for quality seed production. It can be produced by involving farmers of the same village through seed village concept.